1972
DOI: 10.1136/oem.29.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of newspaper workers from lung cancer and bronchitis 1952-66

Abstract: 1972). Brit. J. industr. Med, 29, 1-14. Mortality of newspaper workers from lung cancer and bronchitis 1952-66. The mortality experience of 3 485 men who worked full-time in the newspaper printing industry in London and Manchester and died in the period 1952-66 has been analysed for occupation and cause of death.There was an excess of deaths from cancer of the lung and bronchus (I.C.D. 162, 163) in printing trade workers as a whole compared with the male population ofthe region in which they worked, adjusted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1972
1972
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…No raised mortality patterns are found in any subgroup analyses for this study. Table 5 gives the observed and expected deaths, SMRs, and 95% confidence intervals for malignant neoplasm of the kidney in the distribution center study by company and 11 other deaths where malignant neoplasm of the kidney is a contributory cause of death (4 of whom are drivers). Leukemia.…”
Section: Mortality Resultsmentioning
confidence: 99%
“…No raised mortality patterns are found in any subgroup analyses for this study. Table 5 gives the observed and expected deaths, SMRs, and 95% confidence intervals for malignant neoplasm of the kidney in the distribution center study by company and 11 other deaths where malignant neoplasm of the kidney is a contributory cause of death (4 of whom are drivers). Leukemia.…”
Section: Mortality Resultsmentioning
confidence: 99%
“…(38-228) 16 12 4 129 (74-209) 12 second period. This higher mortality in the second follow up period was reflected in many of the individual groups of neoplasms, for example, malignant neoplasms of the oesophagus, stomach, liver and gall bladder, pancreas, lung, and bladder.…”
Section: -7 105mentioning
confidence: 99%
“…In particular an increased risk for urinary bladder cancer has been reported in several studies (11,(17)(18)(19)(20)(21), although no association was reported in other investigations (12,15,22). In addition, several studies have reported an increased risk of lung cancer (8,17,(23)(24)(25), while other studies have failed to demonstrate any elevated risk (2,26).…”
mentioning
confidence: 98%